Be Aware of Thyroid: Edukasi Hipotiroidisme pada Remaja di MA-Alfarisy - Muhammad Deri Ramadhan; Theophylia Melisa Manumara; Adinda Putri Eriyana; Afifah Azahra; Anggun Nadila; Anggraeni Lestari; Bagas Dinan Maulana; Dina Alipiya; Faiza Sausan Karinda; Naesyha Nirmalasari; Salsa Nurliawati; Salsa Putri Nabil; Siti Jenab Andreani; Zahra Alifannisa (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Hypothyroidism is a condition of disorders in the thyroid gland characterized by low production of thyroid hormones (T3 and T4), causing a decrease in the body's metabolism. This condition can cause various symptoms such as fatigue, weight gain, dry skin, and growth disorders in adolescents. Education about hypothyroidism is important to be done early on to increase awareness and prevention. This health education activity aims to increase adolescents' knowledge about hypothyroidism at MA Al-Farisy. The method used is an interactive method with pre-test stages, material delivery, discussion, and post-test. The activity was held on March 12, 2026 involving 20 participants. The results showed an increase in knowledge after education, marked by an increase in scores from pre-test by 10% to post-test by 15%, and the level of understanding reached 50%. However, the level of activity of participants is still relatively low (25%). Overall, this health education has a positive impact on improving adolescents' knowledge and understanding of hypothyroidism, although further efforts are needed to increase participants' active participation.